Occupational segregation, selection effects and gender wage differences: evidence from urban Colombia - Castro, Jairo Guillermo Isaza (Universidad Pedagógica y Tecnológica de Colombia, 2014)
This paper assesses the effects of occupational segregation on the gender wage gap in urban Colombia between 1986 and 2000. The  empirical methodology involves a two step procedure where by the occupational distributions ofworkers by gender aremodelled using a multinomial logit model in the first stage. In the second stage, the multinomial logit estimates are used not only to derive a counterfactual occupational distribution of women in the absence of workplace discrimination but also to correct for selectivity bias in thewage equations for each occupational category using the procedure suggested by Lee (1983). Besides the explained and unexplained components in conventional decompositions of the gender wage gap, this methodology differentiates between the justified and unjustified effects of the gender allocation ofworkers across occupational categories. The results for urban Colombia indicate that controlling for selectivity bias at the occupational category level is found to be relevant in all years reviewed in this study. They also suggest that a changing composition of the female labour supply in terms of un observables (i.e., ability and motivation) is playing a role in the dramatic reduction of the observed wage gap.